THE INFLUENCE OF SOCIAL MEDIA, E-COMMERCE, AND WEBSITES ON THE PERFORMANCE OF THE ACEHNESE SONGKET MICRO-BUSINESS HOUSEHOLD INDUSTRY KREASI JASMANI - Khairuman, Khairuman; Novita, Rita; Zahraini, Zahraini; Fandi, Rajif (Seminar Nasional Pendidikan, Teknologi, dan Kesehatan (TEKAD), 2025)
The use of digital technology such as Social Media, E-Commerce and Websites can affect the performance of the Micro-Business Home Industry. This study aims to determine the effect of social media, e-commerce and websites on the performance of the Micro-Business Home Industry in Aceh Kreasi Jasamani Songket. This study is an associative study with a quantitative approach. This study consists of three independent variables, namely Social Media (X1), E-Commerce (X2) and Website (X3) and one dependent variable, namely the Performance of IRT-UM (Y). The population in this study were Micro-Business Home Industry Actors in Aceh Besar. The sample was taken using a purposive sampling method with the criteria of songket buyers so that a sample of 40 buyers was obtained. Data were obtained by distributing 40 questionnaires to buyers of Aceh Kresi Jasri songket. The questionnaires that were returned and could be used were 40 questionnaires. The data were analyzed using SPSS 22 with the classical assumption test and multiple linear regression. The results of this study indicate that social media, e-commerce and websites do not have a significant effect on the performance of IRT-UM. The results of this study also show that the independent variables (social media, e-commerce and website) are able to influence the dependent variable (IRT-UM performance) by 18.9% while the remaining 81.9% of IRT-UM performance is influenced by other variables outside the regression model used in this study.